Upconversion NaLuF4 fluorescent nanoprobes for jellyfish cell imaging and irritation assessment of organic dyes1. Issue 23 (21st June 2015) - Chen, Zenghui; Wu, Xiaofeng; Hu, Shigang; Hu, Pan; Yan, Huanyuan; Tang, Zhijun; Liu, Yunxin
<x xml:space="preserve">Abstract</x> Upconversion NaLuF4 nanoprobes with intense visible fluorescence and good biocompatibility have been successfully constructed for assessing the irritation of trace organic molecules in jellyfish cells based on the LRET process.